Eerste Daar - Gordon, Will (Scientia Militaria - South African Journal of Military Studies, 2021)
In the introduction to his book, Van der Waals claims that the book is largely based ona manuscript that he wrote for his children about 15 years ago, and he acknowledgesthat it is not an academic work.564 With this disclaimer of sorts, Van der Waals firmlyplaces his book in the memoire segment of recent South African military historiography.While this is true – the book certainly reads like a memoire – Van der Waals managesto incorporate much more than just personal reflections and recollections in his work.Perhaps due to his academic background, his narrative is lifted above the proliferationof recent memoires by South African Defence Force (SADF) soldiers by occasionalanalyses and opinions interspersed throughout the book.